PENGARUH NON PERFORMING LOAN (NPL) TERHADAP PENYALURAN KREDIT PADA BANK UMUM YANG TERDAFTAR DIBEI PADA PERIODE 2018-2022 - Mulyani, Neng; Purnomo, Hadi (JEMBA, 2024)
Banks as a financial services sector are a bridge institution to receive and distribute public funds. Funds distributed by banks to the community as a form of convenience to obtain loan capital which can also be referred to as credit. Credit disbursement carried out by banks also has the risk of non-performing loans. Non-performing loans are ratios to assess the ability of banks to cover the risk of default on loans by borrowers. This study aims to determine the Effect of Non-Performing Loans (NPL) on Credit Distribution at Commercial Banks listed on the IDX in the 2018-2022 Period. This study uses Non-Performing Loan Objects with indicators of less current, doubtful and stuck credit obtained from the financial data of commercial banks listed on the Indonesia Stock Exchange. The research method used for this study is a quantitative research method whose data is taken from secondary data, namely the financial statements of each bank. The results of the study are expected to provide insight into how the level of Non-Performing Loans affects credit distribution, as well as provide recommendations for the Company's management in managing optimal credit distribution.